Developing a Bilingual Travel Pattern "Surabaya Cultural Heritage" - Putri, Violitaradika; Rina Rachmawati (Journal of Event, Travel and Tour Management, 2025)
Surabaya, known as the City of Heroes, possesses vast potential in cultural heritage tourism. The purpose of this study is to develop a bilingual travel pattern entitled “Surabaya Cultural Heritage”. The need for this study aims to improve Surabaya’s image as a cultural tourism destination while supporting the increase in local and foreign tourist visits to Surabaya for the purpose of vacationing and supporting the Surabaya government's efforts in maximizing the tourism sector. The objective is to create an informative, accessible, and attractive guide that aligns with government efforts to boost the tourism and creative economy sectors. This travel pattern is presented bilingually (English-Indonesian) to meet the linguistic needs of a wider audience. This study is supported by the theory of travel pattern, which explains the structured movement of tourists to maximize experiences. One relevant previous study by Hardiyanti (2021) succeeded in creating a bilingual guidebook for Kampoeng Heritage Kajoetangan that enhanced visitor engagement. The study used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), employing qualitative methods such as observation, interviews, expert validation (four expert validators: content, language, design, and media), and field testing involving 50 respondents. The results of the travel pattern indicate that the bilingual travel pattern was well-received, effectively helping tourists navigate and understand Surabaya’s cultural heritage sites. Discussion of findings reveals that the product improves destination accessibility and tourist experience, especially through route recommendations and QR code integration. The study concludes that such a tool supports cultural tourism and can act as a promotional medium. The writer suggests future development includes adding more languages and incorporating interactive digital features to expand outreach and engagement.